The Production Cost and Productivity Management for Snakeskin Gourami Fishery of Large Scale Farming, Samut Prakarn Province: The Production Cost and Productivity Management for Snakeskin Gourami Fishery of Large Scale Farming, Samut Prakarn Province - youyong, wichuta; Pootrakul , Primsiri; Laongnual, Pranom; Limphaisal, Nitaya (Business Administration and Management Journal Review, 2020)
The associated objective of this research is study on the cost and productivity that is suitable for the just price on the gourami farmers of the big farm in Samut Prakarn Province.This research is used that the mixed method as a research tool for analyzing the data (total cost, average cost, income and productivity). This research framework contains the big farm (740 Rai) that has 26 farmers. The results showed that the total cost of the 3rd form of farming (supplemented with Napier grass) was the least cost, 4,487 Baht per Rai. The fixed cost was to make a big impact on the land rent and renovated pond. The highest overall productivity (4.74) which was consistent with labor productivity and energy productivity. The results suggested that increases in productivity could be implemented by exchanging knowledge management through public participation in snakeskin gourami fishery of large scale farming. The organization of farmer groups in Samut Prakarn Province could be applied to the benefit of aquaculture in the future.